SISTEM MANAJEMEN MUTU PENGAWASAN PEKERJAAN LAPIS PEREKAT JALAN PROVINSI DI PROVINSI KEPULAUAN RIAU - Suji Hartanto; Agus Taufik Mulyono (Himpunan Pengembangan Jalan Indonesia (HPJI), 2018)
Abstract Early damage to road surface layer before the end of road planing life is frequently found in the field of road construction. Road operators always indicate that the main cause of the damage is the overloading of heavy vehicles; however, the facts on the field indicate the existance of another cause that has never been disclosed, i.e. the disobedience of implementing contractor to the implementation of quality management system. This study aims to analyze the contribution of factors that affect the implementation of the work and to propose a method to assess the performance achievement of pavement asphalt work quality in the field. The data used in this study were collected using a questionnaire survey distributed to PPK (Contracting Agency), contractor and supervisory consultants in Riau Islands Province. One of the asphalt pavement works investigated in this study was the tack coat work. Data were analyzed using Structural Equation Modeling (SEM) Analysis. Based on the result of analysis, factors influencing the implementation of tack coat work were subcomponent of preparation (contribute to 75.7%), subcomponent of material and equipment (contribute to 76.9%), and subcomponent of job and maintenance implementation (contribute to 97.9%). The cummulative score of performance achievement was 79.41%, classified as medium category. Keywords: tack coat, early damage, surface layer, road construction, asphalt pavement Abstrak Kerusakan dini pada lapis permukaan jalan sebelum batas akhir umur rencana sering ditemui pada konstruksi jalan. Penyelenggara jalan selalu mengatakan bahwa penyebab utama kerusakan adalah kelebihan beban gandar kendaraan berat, tetapi fakta di lapangan menunjukkan bahwa ada penyebab lain yang tidak pernah diungkapkan, yaitu kontraktor pelaksana tidak patuh terhadap penerapan sistem manajemen mutu. Penelitian ini bertujuan menganalisis kontribusi faktor-faktor yang mempengaruhi pelaksanaan pekerjaan dan membuat cara penilaian capaian kinerja mutu pelaksanaan pekerjaan perkerasan beraspal di lapangan. Data yang digunakan pada penelitian ini diperoleh dari survei kuesioner kepada Pejabat Pembuat Komitmen, kontraktor pelaksana, dan konsultan pengawas di Provinsi Kepulauan Riau. Salah satu bagian pekerjaan perkerasan beraspal yang diteliti adalah pekerjaan lapis perekat. Analisis data menggunakan Structural Equation Modelling Analyisis. Berdasarkan hasil analisis, faktor-faktor yang mempengaruhi pelaksanaan pekerjaan lapis perekat adalah subkomponen persiapan (berkontribusi sebesar 75,7%), subkomponen bahan dan peralatan (sebesar 76,9%), dan subkomponen pelaksanaan pekerjaan dan pemeliharaan (sebesar 97,9%). Perolehan nilai evaluasi kinerja mutu pelaksanaan secara komulatif adalah sebesar 79,41%, yang termasuk kategori medium. Kata-kata kunci: lapis perekat, kerusakan dini, lapis permukaan, konstruksi jalan, perkerasan beraspal